Estudo de uma válvula L através de números adimensionais - Kuhn, Gabriel Cristiano (Universidade do Vale do Rio dos Sinos, 2016)
L valve is a right angled, L shaped pipe applied to transfer solids between two vessels. The device uses gas injection and pipe geometry for controlling the flow of particulate solids. This kind of non-mechanical valve is used in processes as pneumatic transport lines and circulating fluidized beds. This study aims to develop a new correlation to the solids mass flow rate through dimensional analysis, experimental data and equation fitting. An accurately way to estimate the flow of solids makes easier the valve design and control. This study does not consider the influence of the reactors that an L valve connect, in other words, this approach is limited to the influence of L valve geometry, gas injection and particle properties. A test section was built, comprising two valve diameters (acrylic pipes of 34 and 70 mm). Glass beads will be used as solids (Sauter diameter 0.8 mm, bulk density 1580 kg/m3, group D of Geldart classification) conveyed by air. Dimensionless numbers were calculated (by Buckingham PI theorem) from the variables of the process, then an experimental program was done. Based on experimental data, π_1, π_2 and π_3 values were calculated for various test conditions. Based on the experimental data, an equation fit and a correlation to the solids mass flow rate were obtained. Six correlation were calculated but only three are able to describe the L valve process with a minimum accuracy. Maximum solids flow were achieved for 34 mm L valve, in other words, if aeration rate is increased beyond this point, solids flow decreases.
Keywords: Válvula L; Análise dimensional; Escoamento granular; L valve; Dimensional analysis; Granular flow; ACCNPQ::Engenharias::Engenharia Mecânica